Proceedings of the 35th International ACM SIGIR Conference on Research and Development in Information Retrieval 2012
DOI: 10.1145/2348283.2348459
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-based one-class ensemble for classification problems in information retrieval

Abstract: A number of relevant information retrieval classification problems are one-class classification problems at heart. I.e., labeled data is only available for one class, the so-called target class, and common discrimination-based classification approaches, be them binary or multiclass, are not applicable. Achieving a high effectiveness when solving one-class problems is difficult anyway and it becomes even more challenging when the target class data is multimodal, which is often the case. To address these concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Wang et al exploit the inherent target data structures obtained via hierarchical clustering to create an ensemble of spherical 1‐class classifiers. Further work in using clustering for creating 1‐class classifier ensembles is conducted by Lipka et al, where the authors use the k ‐means algorithm to create an ensemble of OCSVM classifiers. A general‐purpose framework for using clustering for improving 1‐class classification is proposed by Krawczyk et al Their framework consists of 3 parts: the choice of clustering algorithm, the choice of 1‐class classifier, and the choice of how to combine decisions.…”
Section: Challenges In Imbalanced Domainsmentioning
confidence: 99%
“…Wang et al exploit the inherent target data structures obtained via hierarchical clustering to create an ensemble of spherical 1‐class classifiers. Further work in using clustering for creating 1‐class classifier ensembles is conducted by Lipka et al, where the authors use the k ‐means algorithm to create an ensemble of OCSVM classifiers. A general‐purpose framework for using clustering for improving 1‐class classification is proposed by Krawczyk et al Their framework consists of 3 parts: the choice of clustering algorithm, the choice of 1‐class classifier, and the choice of how to combine decisions.…”
Section: Challenges In Imbalanced Domainsmentioning
confidence: 99%
“…It also exploits some additional kind of knowledgewhich classes are the most likely to be confused. Other authors also showed that clustering can be used to simply divide the problem into smaller ones solved independently by a separate classifiers [3,8]. In C k RBF, instead of splitting data and analyzing the output of several classifiers, we propose to include all the information gained through clustering into one, generic classifier.…”
Section: Related Workmentioning
confidence: 99%
“…Clustering methods in information networks [1] become more and more popular in recent years. One can discover much interesting knowledge from the information networks by using appropriate clustering methods, and the clustering result can also be used in many fields such as information retrieval [2] and recommendation systems [3]. In particular, the real world information networks are often heterogeneous [4], which means in these networks objects and links between these objects may belong to different types.…”
Section: Introductionmentioning
confidence: 99%